Survival outcomes of 220 consecutive patients with three‐staged thoracoscopic esophagectomy. Issue 8 (6th November 2015) - Noshiro, H.; Yoda, Y.; Hiraki, M.; Kono, H.; Miyake, S.; Uchiyama, A.; Nagai, E.
Summary: Patients with thoracic esophageal cancer are often treated by minimally invasive esophagectomy. However, the long‐term survival benefits of minimally invasive esophagectomy remain unclear. Two approaches are available for thoracoscopic surgery: one with the patient in the left lateral decubitus position (LLDP), and the other with the patient in the prone position (PP). We investigated the survival benefit of thoracoscopic esophagectomy according to the tumor stage and patient position during the thoracoscopic procedure. We reviewed the records of 220 consecutive patients with esophageal cancer treated from 1998 to 2012. In total, 146 and 74 patients were treated with thoracoscopic esophagectomy in the LLDP and PP, respectively. No patients were initially proposed to be candidates for esophagectomy by thoracotomy during the study period. Data collection was performed with a focus on survival and recurrent disease. Among all the 220 patients, the overall 5‐year survival rates were 83.7%, 74.1%, 45.5%, 78.6%, 44.2%, 29.4% and 24.3% in the patients with pStage IA, IB, IIA, IIB, IIIA, IIIB and IIIC disease, respectively. Despite the greater number of dissected mediastinal lymph nodes in the PP procedure, there were no significant differences in the survival curves between the LLDP and PP procedures. The long‐term results of thoracoscopic esophagectomy are comparable and acceptable. The PP procedure was not confirmed to offer a superior survival benefit to the LLDP procedure in this retrospective study.